An Assessment of Competencies of the Adult Education Facilitators Through Valid Pack: A Case Study of India - P. Adinarayana Reddy; D. Uma Devi (University of Sofia, 2013)
India being the most populous countries, has taken initiatives to qualify the human resources by implementing various educational programmes from time to time. Adult education is in operation at different levels for different sections of the population. The Saakshar Bharat is an Adult Education Programme which is an extension of National Literacy Mission intended to impart functional literacy to 70 million illiterates in the age group of 15 years and beyond. In addition, it is to cover 1.5 million adults under basic education programme and an equal number under vocational (skill development) programme. The functionaries involved are of heterogeneous in their qualifications and competencies. The functionaries involved in Saakshar Bharat are administrators (Director, Deputy Directors, Assistant Directors, Project Officers etc.), facilitators (Supervisors, Mandal Coordinators), Adult Literacy Teachers (Literacy Educators, Village Coordinators). There are no clear-cut prescriptions for the qualifications/ competencies for the functionaries working at grass root level viz., facilitators and adult teachers. Very few attempts have been made to develop the tools for assessment of the competencies of adult education facilitators and to measure them. The present paper provides an insight into the assessment of the adult education facilitators competencies by using valid pack, an instrument developed in the European context. It also study the competencies of the facilitators based on self ratings, external observer's ratings and consolidated ratings i.e., and studied the relationship be-tween competencies and personal characteristics of the Adult Education Facilitators.